Entre conflits et coopération - Pauline Fabre; Pierre-Yves Le Meur; Alexander Mawyer; Tamatoa Bambridge (Revue d'anthropologie des connaissances)
Across Oceania, at the same time that coral reef ecosystems are confronting profound global environmental changes, emergent conservation policies are creatively implementing marine protected or managed area governance that demonstrates multiple forms of mixing and interaction between distinct normative regimes (formal/informal, local/State). In this article, we focus on the re-emergence of rāhui, a traditional mode of marine and terrestrial resources management, as a contemporary system for the protection of reef environments in French Polynesia with strong cultural roots. Abolished following Māʻohi (Indigenous Tahitian) conversion to Christianity of at the end of the 18th century, rāhui reappears today in Tahiti as a powerful tool for the conservation of marine resources in the face of environmental changes which threaten the wellbeing of island communities. In Teahupo’o, on Tahiti’s southern coast, contemporary rāhui presents itself as a new conservation policy mobilizing both local and scientific knowledge and institutional legal frameworks with pretension to universal applicability, thus exemplifying the emergence of what we identify as a “hybrid” resource governance. We propose to highlight the hybridization processes at work in this governance form, which, against a background of cooperation, finds itself plunged into the heart of tensions and conflicts specific to the cultural practice of rāhui.